(untitled) (Journal of Economic Research & Business Administration, 2015)
The analysis is carried out and receivables concept issues and its classification are considered in given article. In general, the author’s approach is offered which supplements and specifies the definition of receivables concept. In the conditions of market economy in economy of Kazakhstan one of the basic problems has got a maintenance of circulating assets’ efficient control at the level of economic entity (transactor unit). For working out of receivables’ effective control system on the economic entity (transactor unit) it is important to be defined with receivables concept. Obligation definition is given in article 268 of the Civil Code of Republic Kazakhstan according to which «owing to the obligation one person (debtor) is obliged to make certain action as that in favour of other person (creditor): to transfer property, to perform work, to pay money, etc. or to refrain from certain action, and the creditor has the right to demand from the debtor of execution of its duty». For the fullest understanding of essence of concept «receivables», it is necessary: 1) to define the list of the bases of receivables occurrence; 2) to establish the list of possible debtors. In the conclusion, it has been defined, that receivables are obligations of legal entities, natural persons and other counterparts before the given economic entity (transactor unit).